Implementing the EU HTA regulation: Insights from semi-structured interviews on patient expectations, Belgian and European institutional perspectives, and industry outlooks - Desmet, Thomas; Brijs, Maud; Vanderdonck, Frank; Tops, Sven; Simoens, Steven; Huys, Isabelle (Frontiers in Pharmacology, 2024)
Introduction: The goal of the Health Technology Assessment (HTA) Regulation 2021/2282 is to establish a more harmonized HTA framework, fostering member states cooperation and enabling equal patient access to innovative health technologies in Europe. This research aimed to assess the impact of the regulation on national HTAs, the strategic implications for health technology developers, and its influence on price and reimbursement negotiations. Methods: A scoping literature review encompassing peer-reviewed literature as well as grey literature was conducted. Between February and March 2023, semi-structured interviews (n = 20) were performed with stakeholders from Belgian governmental institutions, European institutions, advanced therapy medicinal product developers, academics, and sickness funds. The interviews were analyzed using the framework analysis method. Results: Numerous steps, such as the development of implementing acts and procedural guidelines remain to be taken. At member state level, national/regional HTA bodies and payers must act to adopt the new concepts of Joint Scientific Consultations (JSC) and Joint Clinical Assessments (JCA) within their national legislation, as well as revise their timelines and prepare for interactions at a European level. Compiling a harmonized PICO (Population, Intervention, Comparator, and Outcome), adapting local procedures, and increasing capacity to actively take part in the JSC and JCA are seen as primary barriers by several stakeholders. Training and education will help HTA bodies, payers, and health technology developers to participate in the European processes. Conclusion: While practical and legal challenges were identified, recommendations (such as actively preparing for the upcoming changes and increasing capacity while providing training) were provided to adapt national and European procedures to the needs of the HTA Regulation 2021/2282. The importance of fostering collaborations and aligning local HTA procedures with the new way of working set out by the Regulation was demonstrated with this study.